Effects of female obesity on conception, pregnancy and the health of offspring - Wei, Wei; Zhang, Xing; Zhou, Baotong; Ge, Bo; Tian, Jing; Chen, Jian (Frontiers in Endocrinology, 2022)
As we all know, female obesity has become a global epidemic, which is usually accompanied with endocrine and metabolic disorders. Obese women are more likely to experience reproductive problems, including infertility, embryonic developmental defects and abnormality in offspring. Female obesity is a complex multifactorial condition, where there are many mechanisms involved in the effects of overweight and obesity on the development of these reproductive disorders. The insulin resistance, hyperinsulinaemia and hyperandrogenism, lipotoxicity and inflammation are important mechanisms. However, the precise mechanism concerning their correlation is still unclear. Fortunately, weight loss methods have been found to reverse the effects of maternal obesity on the fertility, fetus and offspring.